Using the Lean Tissue Index (LTI) as a predictor variable for bone mineral density of elite, adolescent, female cross-country runners - Bonis, M. P.; Loftin, M.; Sothern, M. S. (Journal of Sport and Human Performance, 2017)
Purpose: Determine the best body-composition variable for predicting bone mineral density (BMD) in the sub-population, which included body weight (WGT), lean tissue (LT), body mass index (BMI), body fat (BF), lean tissue index (LTI = LT/Height²), and body fat index (BFI = BF/Height²).